ENCYCLOPAEDIST ALOVIDDIN ALI IBN MUHAMMAD KUSHCHI AND HIS WORK ON "ASTRANOMY" - Safarov Bobomurod Sobir o’g’li (Galaxy International Interdisciplinary Research Journal, 2022)
The article tells about the difficult life of Ali Kushchi on the path of science and his book "Astronomical Treatise". The life of our scientist has been little studied, and it is safe to say that his Astronomical Handbook was one of the founding stones of modern European astronomy.